Evaluation of the cleaning efficiency of the isthmus using different rotary instrumentation techniques (In vitro study) - Zuha A Jaber; Hussain F Al-Huwaizi (Journal of Baghdad College of Dentistry, 2015)
Background: The aims of the study were to evaluate the unclean/clean root canal surface areas with a histopathological cross section view of the root canal and the isthmus and to evaluate the efficiency of instrumentation to the isthmus using different rotary instrumentation techniques. Materials and Methods:The mesial roots of thirty human mandibular molars were divided into six groups, each group was composed of five roots (10 root canals)which prepared and irrigated as: Group one A: Protaper system to size F2 and hypodermic syringe, Group one B: Protaper system to size F2 and endoactivator system, Group two A:Wave One small then primary file and hypodermic syringe, Group two B:Wave One small then primary file and endoactivator system, Group three A: step back technique to size 25 file as MAFand hypodermic syringe, Group three B: step back technique to size 25 file as MAFand endoactivator system . All the roots were sectioned at 2mm, 6mm ,12mm from the apex and studied by histopathological cross section. The degree of cleaning of each section was measured by the use of Autocade 2004 software system. Result :the least uncleaned isthmus surface area at coronal, middle and apical section was found by the Protaper system with endoactivator which represented the mean of the percentage of uncleaned surface area of 16.87%, 14.32% and 9.55% respectively. The system that produced least uncleaned canal wall was by Protaper system with endoactivator at coronal ,middle ,and apical sections of 12.21%, 9.14% and 18.55% respectively . The mean of highest percentage of increased canal diameter which was Protaper system, Wave One system and then step back. The comparison between the groups in the means which showed that the highest percentage of decrease in isthmus area was with the Protaper system, Wave One system and lastly the step back. Conclusions:The Protaper system with endoactivator was the best system in canal and isthmus cleaning.